Necrotizing Epididymo-Orchitis: A Rare Manifestation of COVID-19 - Ali Tavoosian; Sana Ahmadi; Seyed Mohammad Kazem Aghamir (Case Reports in Urology)
Epididymo-orchitis is an infection of the epididymis and testis, one of the most common urogenital infections. It can be seen at any age. It is caused by sexually transmitted microorganisms and nonsexual transmitted pathogens. Viruses such as mumps and cytomegalovirus can also cause epididymo-orchitis. During the COVID-19 pandemic, in case of abnormal clinical manifestations of COVID infection and inadequate therapeutic response to the routine therapies, this disease with unusual manifestations should be considered. The case introduced in this paper is a 55-year-old man referred to a urology clinic with typical clinical presentations of epididymo-orchitis. Diagnosis by color Doppler examination and ultrasound also confirmed epididymo-orchitis. The patient underwent appropriate and routine treatment for epididymo-orchitis. Because of the lack of adequate clinical response and the continuation of fever and the development of scrotal lesions and the results of the control ultrasound, which suggested rupture of the tunica albuginea capsule, he underwent surgical exploration and subsequent orchiectomy. Due to the unconventional conditions and the usual culture and pathology, COVID-19 PCR was also performed on the tissues. The PCR showed tissue infection with COVID-19. The patient’s clinical condition improved with an orchiectomy, the fever stopped, and he was discharged in a good general condition. It should be noted that before referral to the urology clinic and during hospitalization, evaluation, and treatment, the patient had no evidence in favor of respiratory tract infection with the coronavirus.